Influence of meteorological variables on PM2.5 concentrations in cities heated with solid fuels: A case study from Temuco, Chile - Martínez-Soto, Aner; Jentsch, Mark F.; Martinez-Gallegos, Victoria; Duchêne, Jonas; Zipf, Alexander (Atmospheric environment: X, 2026)
Understanding how meteorological conditions influence fine particulate matter (PM2.5) is crucial in cities where residential biomass combustion is a dominant emission source. This study analyses the effects of temperature, wind speed, relative humidity, atmospheric pressure and precipitation on PM2.5 concentrations during the 2019 winter heating season in Temuco, Chile — a city largely dependent on wood for space heating. Data from 11 monitoring stations reveal that PM2.5 levels increase with low temperatures and wind speeds, showing inverse correlations with both, temperature (r = −0.36 to −0.09) and wind speed (r = −0.30 to −0.24). Atmospheric pressure displays a weak positive correlation (r = 0.03-0.30), while humidity and precipitation show variable, site-specific effects. Extreme pollution episodes with PM2.5 >500 μg/m3 coincide with periods of meteorological stability and an increased need for space heating. These results demonstrate that high PM2.5 concentrations arise from the combined effect of strong local emissions and meteorological conditions that inhibit dispersion. The findings provide quantitative evidence to support weather-based air quality forecasting and targeted emission reduction strategies for biomass-dependent urban areas.
Online veröffentlicht: 22. November 2025, Artikelversion: 1. Dezember 2025
Gesehen am 05.01.2026